LEMBAGA PERKREDITAN MASA KOLONIAL - Haryono Rinardi (Faculty of Humanities, Jember University, 2012)
By employing historical method, this article explains formal credit institutions in Indonesia during the Dutch colonial period especially in rural area. The study is focused on the development of three credit institutions emerging during the colonial period that operated under the volkscredietwezen supervision. Before the presence of volkscredietwezen, there had been traditional credit systems among the the society. In rural areas, the people needed loans because it was hard for them to obtain cash money. Lumbung Desa, Bank Desa, and People Bank constituted formal credit institutions in charge of serving the people’s need of loans during the colonial period. One of the interesting things is that there was a connection between the economic development of the society and credit institutions. Keywords: volkscredietwezen, small credit, rural area, colonial era